Silicon distribution in leaves and roots of rice and maize in response to cadmium and zinc toxicity and the associated histological variations. Issue 1 (19th January 2021) - Janeeshma, Edappayil; Puthur, Jos T.; Ahmad, Parvaiz
Abstract: At present, the levels of cadmium (Cd) and zinc (Zn) in arable land are high and affect the growth and development of important food crops, including rice and maize. However, the application of silicon (Si) in contaminated areas increases the metal tolerance potential of these plants. This work aimed to study the variations in the distribution pattern of endogenous Si in various tissue regions in roots and leaves of rice and maize exposed to cadmium (Cd) and zinc (Zn) stresses. For these experiments, 45 day‐old rice (var. Varsha) and maize (var. CoHM6) seedlings were treated with 1.95 g Zn and 0.45 g Cd kg −1 soil. Under Cd stress, the distribution of Si was high in the cortical region of the root, but under Zn stress, the highest Si deposition was found in the endodermis. In leaves, Si deposition was high in both the mesodermis and stelar regions of Cd‐treated plants but more Si was deposited in the mesodermis tissue of Zn‐treated plants. Heavy metal (Cd and Zn) accumulation and Si deposition showed a strong negative correlation in the roots of rice and maize plants. Complexation with metal ions and redistribution of Si were considered the major mechanisms in Si‐mediated mitigation of Cd and Zn stress. Cd‐ and Zn‐induced anatomical changes, such as endodermal thickening, deposits in the xylary elements and aerenchyma formation in the roots of rice and maize, were also associated with the Si distribution.